Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Kepuasan Konsumen di Kejaksaan Negeri Karawang - Juliyanti, Tiara Alvina; S, Sungkono (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In an era of social dynamics, the demand for quality and transparent services is increasingly becoming the main focus. Excellent and reliable public services not only increase bureaucratic efficiency, but also create a positive climate of trust between government agencies and the public. This research aims to evaluate the influence of service quality and trust on consumer satisfaction at the Karawang District Prosecutor's Office. The approach used is quantitative descriptive, with data collected through research instruments and analyzed statistically to test the hypotheses that have been established. The research results show that service quality has a significant effect on consumer satisfaction, with a probability value of 0.005 < 0.05. This shows that the service quality variable has a positive effect on consumer satisfaction at the Karawang District Prosecutor's Office. Apart from that, trust also has a significant effect on consumer satisfaction, with a probability value of 0.000 < 0.05. Thus, both service quality and trust have a significant positive influence on consumer satisfaction. This research highlights the importance of improving service quality and increasing public trust in the District Attorney in creating high consumer satisfaction. It is hoped that these findings can contribute to the development of public service strategies that are more effective and oriented towards community satisfaction.